Acrodermatitis acidaemica. (1st April 2018) - Maguire, C. A.; Chong, H.; Ramachandran, R.; Popoola, J.; Akhras, V.; Singh, M.
Summary: Methylmalonic acidaemia (MMA) is an inborn error of amino acid metabolism that may be associated with cutaneous manifestations mimicking other diagnoses, including staphylococcal scalded skin syndrome (SSSS), psoriasis and acrodermatitis enteropathica. Whether this is due to the underlying metabolic disorder itself or occurs as a consequence of dietary restriction has yet to be elucidated. Skin biopsies typically show histological features shared by a number of other metabolic disorders and nutritional deficiency‐associated diseases. Some presentations, especially SSSS‐like eruptions, may be associated with acute metabolic decompensation. An underlying metabolic disorder, such as MMA, should be considered in a diagnosed adult or undiagnosed child presenting with skin eruptions that resemble those listed above, so that specialist management may be initiated early.